Accurate calculation of absolute free energy of binding for SHP2 allosteric inhibitors using free energy perturbation. Issue 17 (13th April 2022) - Liang, Li; Liu, Haichun; Xing, Guomeng; Deng, Chenglong; Hua, Yi; Gu, Rui; Lu, Tao; Chen, Yadong; Zhang, Yanmin
Abstract : Herein, absolute binding free energies of SHP2 allosteric inhibitors were calculated using FEP method and excellent correlation of 0.96 was obtained, which demonstrates the possibility to accurately predict binding affinity of allosteric inhibitors. Abstract : Accurate prediction of binding affinity is a primary objective in structure-based drug discovery. A free energy perturbation (FEP) method based on molecular dynamics simulation shows great promise for protein–ligand binding affinity predictions. However, accurate calculation of binding affinity for allosteric inhibitors remains unknown and elusive, which hampers the discovery of allosteric inhibitors. Allosteric inhibitors exhibit several significant advantages over orthosteric inhibitors including higher specificity and lower side effects. Allosteric inhibitors against SHP2 are thought to be beneficial not only for diseases related to metabolism, but also for cancer, which make SHP2 a potential drug target. However, high structural sensitivity makes structural optimization of SHP2 allosteric inhibitors face challenges. Herein, we calculated the absolute binding free energy of SHP2 allosteric inhibitors using the FEP method by employing different λ-windows/simulation time sampling strategies. A simulation run with 32 λ-windows/64 ps sampling strategy delivered an excellent correlation ( r = 0.96) and an unprecedented low mean absolute error of 0.5 kcal mol −1 between predicted binding free energies and experimental ones, outperforming the MM/PBSA method. Our study demonstrates the possibility to accurately calculate the absolute binding free energy of allosteric inhibitors using FEP, which offers exciting prospects for the discovery of more effective allosteric inhibitors.